SCIENTIFIC AND THEORETICAL BASIS OF THE DEVELOPMENT OF WOMEN'S ENTREPRENEURSHIP (Scientific journal of the Fergana State University, 2023)
In this article, the social aspects of the entrepreneurial factor in the theoretical concepts of philosophy are studied. In elucidating the social concepts of entrepreneurship, developed foreign socio-philosophical theories were relied on, and they were comparatively analyzed, paying attention to the socio-philosophical theories of philosophers who contributed to the social development of entrepreneurship. This is important in explaining the social aspects of entrepreneurship in the theoretical and methodological concepts of philosophy.